The Effect of Thin Capitalization, Tunneling Incentive, Exchange Rate, Foreign Ownership, and Effective Tax Rate on Transfer Pricing - Ermadiani Ermadiani; Tjandrakirana DP, Rina; Wahyudi, Tertiarto (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to test and find empirical evidence of the influence of Thin Capitalization, Tunneling Incentive, Exchange Rate, Foreign Ownership, and Effective Tax Rate on transfer pricing. The type of data used is secondary data in the form of annual reports of companies listed on the Indonesia Stock Exchange. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2016-2023, and the sampling technique used was the purposive sampling method and obtained a total of 128 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2023. The analysis technique used is panel data regression analysis, previously a panel data estimation test, Chow test, Hausman test and Lagrange Multiplier (LM) test will be carried out to determine the model approach that will be used between common effects, fixed effects and random effects. Next, a hypothesis test is carried out to answer the hypothesis that has been formulated using the Partial Test and Coefficient of Determination (R2).